(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2007)
Limited South African research could be found in the existing literature regarding young people’s attitudes towards their parents – and particularly their fathers, who play a vital role in their development in terms of the provision of emotional support and guidance. The main objective of this project was therefore to determine how students from different racial groups feel about their fathers. A sample consisting of 152 students of different races at the University of the Free State, participated in the study. The results indicated that the black students were significantly less positive in their attitudes towards their fathers than were the coloured and white students. It was also found that the English-speaking group differed significantly from the Afrikaans-speaking students, in that the latter were significantly more positive in terms of their attitudes towards their fathers. No differences were found relating to gender and age.